Free volume manipulation of a 6FDA-HAB polyimide using a solid-state protection/deprotection strategy. (6th January 2021) - Lin, Sharon; Joo, Taigyu; Benedetti, Francesco M.; Chen, Laura C.; Wu, Albert X.; Mizrahi Rodriguez, Katherine; Qian, Qihui; Doherty, Cara M.; Smith, Zachary P.
Abstract: Tert-butoxycarbonyl (t-BOC) is a thermally labile moiety that can be used to protect hydroxyl groups on polymers. In this study, t-BOC was appended onto a polyimide consisting of 2, 2′-bis-(3, 4-dicarboxyphenyl) hexafluoropropane dianhydride (6FDA) and 3, 3′-dihydroxy-4, 4′-diamino-biphenyl (HAB), after which the polymer was formed into self-standing films. Solid-state thermal treatments were performed to systematically remove t-BOC moieties to alter the physical packing structure and concomitant gas transport properties of the polymer. Despite performing deprotection reactions well below the glass transition temperature of 6FDA-HAB (~300 °C), this free volume manipulation (FVM) approach produced only subtle differences in polymer density, fractional free volume, average free volume element size, and gas transport properties relative to the unprotected polymer. While these findings suggest that thermally removing covalently bound functional groups from polymer films can be used to manipulate free volume and gas transport performance for glassy polymers, more robust polymer systems than linear polyimides are required to preserve the nascent free volume architecture generated from this approach. Graphical abstract: Image 1 Highlights: Polymer packing was studied via thermal treatments on functionalized 6FDA-HAB. Thermal treatments below the polymer Tg can lead to polymer chain mobility. FFV and transport property changes show that extent of treatment affects packing. PALS suggests that packing may change from mechanisms besides densification.